Factors Influencing Indonesian Mobile Gamers on Repurchase Intention in Freemium Mobile Game With Perval - Aprianingsih, Atik; Nusantara, Bambang D.A.; Maharatie, Andhiny Puspa; Widyasthana, G.N. Sandhy (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: The mobile gaming industry has experienced remarkable growth in recent years. However, the majority of Indonesian gamers' spending goes to foreign developers, with only 1.2% of the players' total spending of $1.1 million going to local developers. Purpose: This study aims to analyze the factors that influence consumers' repurchase intentions when purchasing virtual items in the game Mobile Legends. Design/methodology/approach: This study uses the Mobile Legend case study to inspire local game developers to better compete with globally popular games. A quantitative research method was employed to test the hypothesized relationships between the constructs using a sample size survey of 390 Indonesian Mobile Legends players.Findings/Result: Findings from descriptive analysis of tested variables provided a balanced view between strengths in the gaming experience, such as high emotional and social value derived from role modeling features, and weaknesses around graphical quality and overall user satisfaction. On the other hand, when we tested the conceptual model using the PLS-SEM approach, we found that factors such as emotional value, price value, quality value, social value, satisfaction, addiction, and loyalty significantly influence repurchase intention has been confirmed. Conclusion: Finally, recommendations including strategies to improve regional cultural representation and the use of price promotions and installment plans to optimize value perception are recommended for Indonesian games aiming to better compete with global game developers.Originality/value (State of the art): This research addresses the existing gap in literature by proposing additional predictors, including addiction and loyalty, to provide comprehensive guidance for mobile game developers in stimulating increased repurchase intentions Keywords: PERVAL framework, satisfaction, repurchase intention, online mobile game, mobile legends